2011
DOI: 10.1177/0333102411425866
|View full text |Cite
|
Sign up to set email alerts
|

Treatment costs and indirect costs of cluster headache: A health economics analysis

Abstract: CH leads to major socioeconomic impact on patients as well as society due to direct healthcare costs and indirect costs caused by loss of working capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 24 publications
4
87
0
3
Order By: Relevance
“…Solomon et al found that patients with CH had significantly lower rates of social activity compared with patients with migraines, in line with our findings [16]. Indirect costs from work disability and lower participation caused by CH impose a significant socioeconomic burden on patients and society [17, 18]. …”
Section: Discussionsupporting
confidence: 90%
“…Solomon et al found that patients with CH had significantly lower rates of social activity compared with patients with migraines, in line with our findings [16]. Indirect costs from work disability and lower participation caused by CH impose a significant socioeconomic burden on patients and society [17, 18]. …”
Section: Discussionsupporting
confidence: 90%
“…However, these studies have all used either generic QoL scales such as the SF-36, or migraine-specific scales that may not necessarily be able to capture the true effects of CH, and may therefore be underestimating the actual impact of the disorder on QoL. Indeed, some instruments specifically ask about suffering in the past four weeks, thus ECH sufferers out of a bout would rate low scores on these scales, even though they may be severely impaired during a bout [9]. Hence, these measures may not provide a true reflection of the actual impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Les patients souffrant d'AVF chronique et d'AVF épisodique en période active ont une perte de productivité plus importante que les patients souffrant d'AVF en dehors des périodes douloureuses et que les migraineux (grade C) [18]. Dans une étude mono-centrique de 179 patients suivis dans un centre tertiaire allemand, les coûts directs moyens sur 6 mois ont été estimés à 5963 D et sont apparus corrélés positivement à la fréquence des crises (grade C) [21]. Ce même travail a montré que 13,4 % de ces patients étaient dans l'incapacité de travailler [21].…”
Section: Comorbidité Psychiatriqueunclassified
“…Dans une étude mono-centrique de 179 patients suivis dans un centre tertiaire allemand, les coûts directs moyens sur 6 mois ont été estimés à 5963 D et sont apparus corrélés positivement à la fréquence des crises (grade C) [21]. Ce même travail a montré que 13,4 % de ces patients étaient dans l'incapacité de travailler [21]. Cet impact professionnel a été également mis en évidence au Danemark avec 30 % d'absentéisme professionnel chez les patients souffrant d'AVF (grade C) [19] et aux États-Unis avec près de 20 % des patients souffrant d'AVF déclarant une perte d'emploi secondaire à leur maladie (grade C) [8].…”
Section: Comorbidité Psychiatriqueunclassified